The morphology of tourism. Planning for impact in tourist destinations. - Xie, Philip Feifan; Gu, Kai (Routledge, 2019)
Morphological research studies the physical form of landscapes, including how landscape structures function and operate, the adaptability of forms, and how functions and forms change over time. Applying the methods and models of morphology to tourism, this innovative book explores some of the complex relationships between tourism and morphological changes in urban and rural destinations across the globe. Tourism-related impacts on the physical environment and sociocultural values surrounding a given destination reflect the need for both theoretical and empirical approaches to strengthen our understanding of the ways in which tourism functions. This study examines key sectors and locations such as coastal tourism, urban tourism, and waterfront redevelopment, which are increasingly important in terms of their influence on sociocultural and morphological transformation. It advocates that awareness of the critical link between temporospatial impacts and morphological progresses is necessary to accommodate changes within a pattern of evolutionary growth. International in scope, employing case studies from Asia, Australasia, the US, and Europe, this book makes a newcontribution to the literature and will be of interest to students and researchers of tourism planning, urban design, geography, environmental studies and landscape architecture.
Keywords: Stadtplanung; Tourismus; Fremdenverkehr; Städtetourismus; Stadtentwicklung; Stadterneuerung; Morphologie; Stadtgestalt; Küste; Historische Stadt; Hafengebiet; Strukturwandel; Stadtumbau; Küstenstadt